Pengaruh e-Service Quality Dan e-Trust Terhadap Keputusan Pembelian Konsumen Pada Produk Dengan e-Satisfaction Sebagai Variabel Intervening - Harris Manurung; Qiven Daud (JOURNAL FOR BUSINESS AND ENTREPRENEURSHIP, 2021)
This study aims to see the effect of e-service quality and e-trust on consumer purchasing decisions on products with e-satisfation as an intervening variable. This research is a quantitative research with a survey method. The population in this study are consumers who have forgotten about the Shopee site more than once. The sampling technique used purposive sampling with a total sample of 215 people. The data technique uses an online questionnaire that has been tested for validity and reliability. The data analysis technique used to answer the hypothesis is path analysis with the help of simple regression and sobel test. Keyword: e-Service Quality; e-Trust; e-Satisfaction;